Arete as Efficacy of Plato's Ontological Transit - Adán, Oscar (1999)
The following paper outlines the contours of arete in the late Plato in association with the ontological transit from 'being' to genesis, starting from the Parmenides· second hypothesis and the Epinomis'" mathematical excerpt." Nonetheless, by introducing the 'necessary reality of genesis' within the eidetic framework, Plato feels torced to postulate 'non-being' within the ontological economy -as may beread in the Sophist- and paradoxically to recognize in it the degree of absolute sameness. How does thisnon-being appear in the midst of the eide? The answer is surprising.